PENGARUH KESADARAN MEREK DAN KEPERCAYAAN KONSUMEN ATAS MEREK TERHADAP KEPUTUSAN PEMBELIAN ULANG PRODUK SMARTPHONE SAMSUNG - Baruno, Agustiawan Djoko; Puji Susanto, Arisca Handri (Jurnal Ilmu Manajemen Advantage, 2018)
This study aims to determine : (1) the influence of brand awareness on the decision to repurchase Samsung smartphone products (2) the influence o brand trust on the decision to repurchase Samsung smartphone products (3) the influence of brand awareness and brand trust on the decision to repurchase Samsung smartphone products (4) dominant factors that influence the decision to repurchase Samsung smartphone product. The data used in the this research are primary. Primary data in this research were obtained from a questionnairen that the measurement using a likert scale and statistically processed using multiple linier regression formula by using SPSS version 23. Based on the result of this research is that Test F variabel X1 (Brand Awareness) and X2 (Brand Trust) simultaneously influence the repurchase (Y). This is evidenced as 53,221 F count > F table 3,13. While the t test, there is no partial influence Brand awareness (X1) on the repurchase decision (Y), it is proved because -1,599 t count â‰¥ -1,99444 t table and Brand trust (X2) have partial influence on the repurchased decision (Y), it is proved because 9,779 t count > 1,99444 t table. Brand trust is the most dominant variabel on repurchased decision (Y) it is proved because 9,779 t count > 1,99444 t table. The magnitude of the influence of the independent variables were analyzed together the dependent variable 58,9 %, while the remaining 41,1 % is influenced by other variables that are not in this research.